1999
DOI: 10.1111/j.1469-7793.1999.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Shift from depolarizing to hyperpolarizing glycine action in rat auditory neurones is due to age‐dependent Cl regulation

Abstract: The mechanisms underlying the development and maturation of inhibitory synapses in the central nervous system (CNS) are still poorly understood. This is mainly due to the fact that inhibitory neurones are mostly interneurones which are diffusely distributed within a brain region. In the adult CNS, fast synaptic inhibition is mediated by the release of GABA or glycine and subsequent activation of GABAA receptors (GABAARs) or glycine receptors (GlyRs). These receptors are ion channels permeable to Cl¦ and, to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
173
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(180 citation statements)
references
References 55 publications
7
173
0
Order By: Relevance
“…These data indicate that MNTB-evoked PSPs are primarily depolarizing up to P3 and hyperpolarizing thereafter. Thus, compared to rats [11] or gerbils [12] MNTB-evoked PSPs in mice become hyperpolarizing 5-7 days earlier, consistent with the somewhat faster maturation of the mouse auditory system [5].Recently, it has been demonstrated that glycine can elicit action potentials (APs) in immature rat LSO neurons [7] suggesting that glycine can act as an excitatory neurotransmitter in the LSO. However, in these studies glycine was applied iontophoretically to the cell body, a somewhat artificial situation because it activates both synaptic, as well as extrasynaptic, glycine receptors.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…These data indicate that MNTB-evoked PSPs are primarily depolarizing up to P3 and hyperpolarizing thereafter. Thus, compared to rats [11] or gerbils [12] MNTB-evoked PSPs in mice become hyperpolarizing 5-7 days earlier, consistent with the somewhat faster maturation of the mouse auditory system [5].Recently, it has been demonstrated that glycine can elicit action potentials (APs) in immature rat LSO neurons [7] suggesting that glycine can act as an excitatory neurotransmitter in the LSO. However, in these studies glycine was applied iontophoretically to the cell body, a somewhat artificial situation because it activates both synaptic, as well as extrasynaptic, glycine receptors.…”
mentioning
confidence: 86%
“…Recently, it has been demonstrated that glycine can elicit action potentials (APs) in immature rat LSO neurons [7] suggesting that glycine can act as an excitatory neurotransmitter in the LSO. However, in these studies glycine was applied iontophoretically to the cell body, a somewhat artificial situation because it activates both synaptic, as well as extrasynaptic, glycine receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vast majority of mature neurons, a low intracellular chloride concentration ([Cl Ϫ ] i ) causes Cl Ϫ influx during channel opening, resulting in hyperpolarization (Eccles, 1966;Kaila, 1994). In contrast, a high [Cl Ϫ ] i in immature neurons results in Cl Ϫ efflux at the resting membrane potential (Zhang et al, 1991;Wang et al, 1994;Obrietan and van den Pol, 1995;Ehrlich et al, 1999;Kakazu et al, 1999). This efflux depolarizes the neurons and can even elicit action potentials.…”
Section: Introductionmentioning
confidence: 93%
“…The time course of refinement follows the development of inhibition in the MNTB -LSO system. As is seen during the development of other inhibitory neurons [14], the Cl 2 reversal potential in neurons of the LSO is relatively positive (2 48 mV) at birth but becomes more negative (2 82 mV) by the time of hearing onset [15]. During the refinement period, therefore, glycinergic and GABAergic inputs depolarize the postsynaptic cell [16], which can produce increases in postsynaptic Ca 2þ concentration and can result in action potentials [17].…”
Section: Excitatory Gabaergic and Glycinergic Synapsesmentioning
confidence: 99%